مخاطر شبكات التواصل الاجتماعي على الهوية الإسلامية وسبل الحفاظ عليها (Al-Qamar, 2022)
This paper discusses the effects of social media on Islamic societies, especially on Islamic identity, which is well established and rooted in origin, source and reference. The aim of the research is to identify the Islamic identity, its characteristics, and the implications of the use of social networks on the features of Islamic identity. And the challenges that faces and pose a threat to Islamic identity. Where the Islamic identity in the era of high-tech giant the most serious challenges that throughout the ages, such as the defamation of Islamic identity to eliminate the components of the entity and signs of power, and contain the ethics of weakness and disintegration and pornography.The study concluded by many results, the attempt to draw the right way out of the negative effects of the social networks on the Islamic identity, and to uncover the external and internal causes that weakened the Islamic identity, the era of modern technology and ways to preserve it. Almighty Allah is the guardian of success and repayment.
Keywords: Islamic identity; social networks; the dangers of network; preserve of Islamic identity